Effect Of Moringa Oleifera Extract On Some Sperm Parameters And Testis In Diabetic Rats - Zainab A. Jaiballah , Naji M. Lji , Fathi B. Alamyel (Journal of Pure & Applied Sciences, 2020)
Abstract  This study aims to demonstrate the effectiveness and ability of the methanolic extract of Moringa oleifera (M. oleifera ) leaves to improve some sperm parameters and testis in diabetic  rats. Twenty healthy adult male Wistar rats divided equally into 4 groups of (n = 5) were used in this investigation. First group represents the negative control, while second group is the positive control, whereas the following two groups represent the treated groups of M. oleifera leaves with a concentration of 300mg/kg and 600mg/kg for 4 weeks. At the end of the experiment, the rats were anesthetized and sperm collected from epididymis to calculate their numbers and abnormalities in them by light microscope. Meanwhile,  the testis was extracted for histological study. The totals of treatment with the extract in the M. oleifera groups showed a significant decrease in the level of fasting sugar (P